High-Resolution, Continuous Method for Measurement of Acidity in Ice Cores - Pasteris, D.; McConnell, J.; Edwards, Peter (American Chemical Society, 2012)
The acid content of ice core samples provides information regarding the history of volcanism, biogenicactivity, windblown dust, forest fires, and pollution-induced acid rain. A continuous ice core analysis allows for collection of high-resolution data in a very efficient manner, but this technique has not been readily applied to the measurement of pH and acidity in ice cores. The difficulty arises because thesample is highly undersaturated with respect to carbon dioxide (CO2) immediately after melting, making it difficult to maintain stable concentrations of dissolved carbon dioxide and carbonic acid (H2CO3). Here, we present a solution to this problem in the form of a small flow-through bubbling chamber that is supplied with a known concentration of CO2. The bubbling action allows for quick equilibration while the small size of the chamber limits sample mixing in order to maintain highresolution. Thorough error analysis provides a measurement uncertainty of ±0.20 µM or ±5% of the acidity value, whichever is greater, and the T95 signal response time is determined to be 1.25 min. The performance of the technique is further evaluated with data from a 63-year ice core from northwest Greenland for which all major ion species were also measured. The measured acidity closely matches the acidity derived from a charge balance calculation, indicating that all of the analytes were measuredaccurately. The performance specifications that we provide are applicable to ice cores with low concentrations of alkaline dust (<500 ppb), which includes the vast majority of ice cores that are collected. To date, the method has not been evaluated with samples containing high alkaline dust concentrations, such as Greenland cores from the last glacial period, where measurement could be made difficult by memory effects as particles coat the internal surfaces of the sample stream